Magnesium, zinc, and chromium - Lukaski, H. C. (1996)
Attempts to examine the relationships between physical activity and magnesium, zinc, or chromium nutritional status have been hampered generally by limitations in experimental design. Overall, the evidence to suggest that physically active individuals have either impaired magnesium or zinc status or improve performance with supplementation of these minerals is equivocal because nutritional status was not examined.